2015
DOI: 10.1039/c4cs00351a
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic biology for the directed evolution of protein biocatalysts: navigating sequence space intelligently

Abstract: Improving enzymes by directed evolution requires the navigation of very large search spaces; we survey how to do this intelligently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
259
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(266 citation statements)
references
References 1,317 publications
3
259
0
4
Order By: Relevance
“…The assumption of randomness in biology generally holds well enough to serve as a useful approximation, but in fact biological variation is not genuinely random; for example, a bias might arise due to mutagenic agents, assortative mating, or in the case of synthetic biology, directed mutation (e.g., Currin, Swainston, Day, & Kell, 2015). Natural selection works by generating numerous possibilities through a process that can be approximated by a random distribution, such that often enough at least one variant is bound by chance to be fitter than what came before, and likely to be amplified in subsequent generations.…”
Section: Biased Variation/directed Mutationmentioning
confidence: 99%
“…The assumption of randomness in biology generally holds well enough to serve as a useful approximation, but in fact biological variation is not genuinely random; for example, a bias might arise due to mutagenic agents, assortative mating, or in the case of synthetic biology, directed mutation (e.g., Currin, Swainston, Day, & Kell, 2015). Natural selection works by generating numerous possibilities through a process that can be approximated by a random distribution, such that often enough at least one variant is bound by chance to be fitter than what came before, and likely to be amplified in subsequent generations.…”
Section: Biased Variation/directed Mutationmentioning
confidence: 99%
“…So, it would appear that natural enzymes are "just good enough" for the function they must perform in a given organism [7]. One might conclude that if they had evolved to their optimum performance then trying to improve them (from a kinetic point of view) would be attempting the impossible.…”
Section: Introductionmentioning
confidence: 99%
“…These are often limited only by the rate of ligand diffusion into the active site (diffusion-controlled rate). Nevertheless, an extensive analysis by Bar-Even et al, of nearly 2000 enzymes, showed that the median maximal turnover rate value over all measured enzymes is about 10 s −1 nowhere close to the values of 10 5 or 10 6 normally associated with catalysts [5,6].So, it would appear that natural enzymes are "just good enough" for the function they must perform in a given organism [7]. One might conclude that if they had evolved to their optimum performance then trying to improve them (from a kinetic point of view) would be attempting the impossible.…”
mentioning
confidence: 99%
“…The sequence complexity is fundamental in protein systems [32,34]. For a typical size of protein domains, say 100 amino acids, there are about 20 100 (∼ 10 130 ) possible sequences with the alphabet built with 20 kinds of amino acids.…”
Section: Sequence-structure Relationship and Diversity Of Sequencesmentioning
confidence: 99%